Funkcjonowanie służb ratowniczych w euroregionie Nysa w obliczu zagrożeń i sytuacji kryzysowych - Piepiora, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This article describes processes of integration of emergency staff in Euroregion Nysa which are very important in the face of existing threats and more important in case of the new crisis situations. New threats can appear in connection with extending of the European Union. Processes of integration are going on all degrees - from local, through regional, to international. Integration of emergency staff in the close environment (local) and far environment (international) is going to origin the Universal System of Detection and Alarm which works against threats and brings the higher level of security for all citizens.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 269-277